Skip or captain? : The changing perception of school management and leadership in Germany - Britta Klopsch; Johannes Gutbrod (International Journal of Educational Administration, Management, and Leadership, 2022)
A changing world needs schools that adapt to changes and support their students to thrive. All related developments are moderated, guided, and also implemented by principals. To do this, they need the support of their staff, but also administrative support from the system. In Germany, the system's support is based on a link between management and leadership through clear task descriptions. The following text asks, on the one hand, what school development means for school leaders. On the other hand, it asks whether school development is perceived differently when schools are at different levels of school development experience. In terms of methodology, qualitative interviews were chosen to provide the best possible insight into personal experiences. We interviewed six school principals and their deputies who are actively engaged in school development for at least five years. The analysis shows two diametrically different types of leadership: The Captain and the Skip. Their role descriptions show that the underlying attitude contributes to empowering those involved for necessary change or to restricting them in such a way that genuine, profound change is prevented. A shift in changing leadership might therefore need open-minded principals and deputies who inspire hearts and minds and let change happen.